1972
DOI: 10.1295/polymj.3.739
|View full text |Cite
|
Sign up to set email alerts
|

Randomly Branched Polymers. II. Computer Analysis of Gel-Permeation Chromatogram

Abstract: An iterative computer method was proposed for estimating the degree of branching and molecular weight distribution simultaneously from a pair of measurements on intrinsic viscosity and gel-permeation chromatography. The validity of the method as applied to randomly branched polymers was tested by using both fractionated and unfractionated samples of branched polystyrenes. It was experimentally concluded that the average number of branch points per unit molecular weight, A, can be determined by this method with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…3 The molecular weight distribution and number-average molecular weight of the polymers were determined from the results of the measurement of intrinsic viscosity and GPC by the method of Kurata et al 5 Results of the polymer analyses are shown in Table 11.…”
Section: Characterization Of Polymersmentioning
confidence: 99%
“…3 The molecular weight distribution and number-average molecular weight of the polymers were determined from the results of the measurement of intrinsic viscosity and GPC by the method of Kurata et al 5 Results of the polymer analyses are shown in Table 11.…”
Section: Characterization Of Polymersmentioning
confidence: 99%
“…Considering the error in A3 originating from the 3-% error in the estimate of the intrinsic viscosity, the lower limit of the estimate of A3 might be 10- 6 in the present analysis. The observed value of A3 for the sample H-1 polymerized to the conversion of 79.2% at 90°C was 1.6 x 10- 5 and Mw was found to be 3.44 X 10 5 • Therefor, this polymer has 5.5 weight-average long-chain branches per polymer chain. The observed value of A3 for H-2 was lower than that for H-1, though H-2 was polymerized to a higher conversion than H-1.…”
Section: Gpc Measurementmentioning
confidence: 87%
“…Kurata, et al, 5 -7 also reported the same method independently, and discussed the limit of reliability by showing an example of the application to branched polystyrene. In the present paper, the amount of long-chain branches in PV A was determined by means of Kurata's method, [5][6][7] and the results were compared with those expected * Leave of absence from Department of Polymer Science, Kyungpook National University, Korea.…”
mentioning
confidence: 99%
“…The method is based on the MWD functions of St~ckmayer'~ and on the expressions for g [eqs. (9) and No viscosity measurements and no iterative procedure are necessary.…”
Section: Prediction Of Gpc Behavior Of Randomly Branched Polymersmentioning
confidence: 99%